Evaluation Of The Implementation Of The Hiv/Aids Counseling And Testing Service Program (Case Study At Cidempet Health Center And Bongas Health Center, Indramayu Regency) - Fauzi, Muhamad; Wahyudin; Yulyanti, Depi; Aliyah (Ann Publisher, 2024)
HIV continues to be a significant global public health problem, claiming 36.3 million lives so far and an estimated 37.7 million people living with HIV by the end of 2020. 16% of all people living with HIV do not know they have HIV. People infected with HIV in 2020 reached 1.5 million lives, and people died reached 680,000 lives. (WHO, 2020). This study aims to evaluate the implementation of HIV/AIDS counseling and testing at the Cidempet Health Center and the Bongas Health Center, Indramayu Regency. The research method used is qualitative with a case study approach. The research informants consisted of 3 primary informants: 1 HIV/AIDS Program Holder of the Health Office, 2 HIV/AIDS Program Holders of the Health Center, and 4 Triangulation Informants: 2 Heads of Health Centers and 2 Recipients of HIV/AIDS Counseling and Testing Services. The data was analyzed through the stages of data reduction, data presentation, and conclusion drawing. This study shows that there is no difference in the implementation of guidance/direction and communication in HIV/AIDS counseling and testing programs before the COVID-19 pandemic was carried out directly and during the COVID-19 pandemic was transferred online. The implementation of work motivation within the health center is not explicitly given. While motivating service recipients at the Cidempet Health Center is good enough, the Bongas Health Center is not. The implementation of human resource performance is still an obstacle due to the shortage of human resources and the allocation of funds, and there are differences in the provision of funding sources for HIV/AIDS counseling and testing activities. The conclusion of this study is that before and after the COVID-19 pandemic, the implementation of counseling and tests experienced differences where counseling visits and tests only accepted patients who were indicated to have HIV, the implementation of Briefing, communication, motivation, human resource performance, and fund allocation had their obstacles. The suggestion in this study is to improve and optimize policies and procedures for HIV/AIDS counseling and testing in Puskesmas.